2012
DOI: 10.3341/jkos.2012.53.6.895
|View full text |Cite
|
Sign up to set email alerts
|

Two Cases of Ocular Complications Caused by Phendimetrazine

Abstract: Purpose:The authors of the present study report treatment experience of acute myopia and branch retinal vein occlusion associated with phendimetrazine, a drug used for weight reduction. Case summary: Case 1: A 32-year-old woman, previously devoid of ocular problems, visited our hospital with bilateral visual disturbance after taking phendimetrazine for weight reduction. Ciliochoroidal effusion and anterior shifting of the lens-iris diaphragm were observed, which resulted in a shallow anterior chamber, myopic s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…Consequently, he concluded that the patient's vision loss was due to vasoconstriction of the posterior ciliary arteries secondary to phentermine use. In addition, Cho et al 7 and Huh et al 8 reported on patients who presented with a central retinal vein occlusion (CRVO) after taking prescribed dosages of phendimetrazine, another sympathomimetic amine used as an appetite suppressant. As a result, based on these case reports, sympathomimetic amines like phentermine may have an adverse physiological effect on the retinal vasculature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Consequently, he concluded that the patient's vision loss was due to vasoconstriction of the posterior ciliary arteries secondary to phentermine use. In addition, Cho et al 7 and Huh et al 8 reported on patients who presented with a central retinal vein occlusion (CRVO) after taking prescribed dosages of phendimetrazine, another sympathomimetic amine used as an appetite suppressant. As a result, based on these case reports, sympathomimetic amines like phentermine may have an adverse physiological effect on the retinal vasculature.…”
Section: Discussionmentioning
confidence: 99%
“… 1 , 2 While studies have shown that this drug is safe, several case reports have demonstrated phentermine being associated with adverse effects including stroke, myocardial infarction, and ischemic ocular diseases. 3 , 4 , 5 , 6 , 7 , 8 In addition, other amphetamine derivatives, especially ones that are abused like methamphetamine and cocaine, have been well documented to have harmful effects on the cardiovascular, neurologic, and psychologic systems. 9 In particular, ocular side effects of amphetamine abuse include mydriasis, decreased accommodation and convergence, visual hallucinations, retinal vasoconstriction and vasculitis, retinal microaneurysms and hemorrhage, and anterior ischemic optic neuropathy.…”
Section: Introductionmentioning
confidence: 99%